La gestión pública local del desarrollo regional local - Vargas Hernández, José G. (2010)
Este trabajo tiene por objetivo analizar los elementos de la gestión pública del desarrollo regional a partir de las condiciones del desarrollo regional y las nociones de desarrollo local y desarrollo sustentable. Bajo estas premisas se avanzan planteamientos esquemáticos en torno a la gestión pública del desarrollo local
This paper has the aim to analyze the features of public management of regional development starting from the conditions of regional development and the notions of local development and sustainable development. Under these assumptions it is advanced some schematic drawings on public management of local development
Keywords: Desarrollo local; Desarrollo regional; Desarrollo sustentable; Gestión pública local; Local development; Regional development; Sustainable development; Local public development